A pátria socialista : a URSS sob o imaginário do PCB (1946-1953) - Alves, Tiago João José (2011)
This research aims to analyze the imagery of the PCB on the USSR. The context chosen is the beginning of the Cold War, from 1946 to 1953, when tensions escalated between the two major powers of the globe, the USA and the USSR. The choice is justified because at this moment, the image of the USSR becomes large as a result of some transformations: the victory over Nazism, communism expansion, progress made by the Five-Year Plans. Stalin became a global character, the Communists have grown across the globe, including Brazil. Dialoguing with Bronislaw Baczko means that the imagination is a set of beliefs and concepts that help to control and to give cohesion to a collective grouping. Analyzed under this formulation, it appears that the PCB was an imaginary about the USSR. This set of symbols serving as a "shield" and "sword." Both served to strengthen the defense of the ideas of the PCB as to advance their positions. The USSR had become a showcase and a paradigm. The partisan press appears as a special place in this imaginary reverberation. Served to galvanize the Communists themselves, winning followers and combat anti-communism. Backed by the newspaper A Classe Operária and Voz Operária, we will investigate how the PCB has built its myths, symbols, rituals and images around the USSR. The PCB sought to assert that the communist project was the best future for mankind, unlike the proposed USA. Therefore, the research does not intend to establish a study on the guidelines of the USSR to the PCB, but rather analyze the image that the party did the Soviet world. The analysis is divided into three chapters. The first one, is an examination of the dawn of the Cold War and its impact in Brazil, the second discusses the trajectory of the PCB and its connection with the Soviets, and the third examines the imagery that the PCB has formulated over the USSR.